Pre-Service Teachers’ Interaction with Learners Using Their Mother Tongue in Linguistically Diverse Classes in Namibian Schools - Mmamoyahabo Constance Makgabo; Alina Kakunde Niipare (Journal of Languages and Language Teaching, 2022)
This article reports on a study conducted in five primary schools in Namibia during teaching and learning in the mother tongue classroom. The aim of this study was to investigate how 30 pre-service teachers used the learners’ home language during their curriculum delivery. The study took place during lessons that included work-integrated learning (WIL) during which the pre-service teachers were assessed by the two lecturers as researchers. The study followed a qualitative approach where data were gathered from classroom observations and semi-structured interviews of pre-service teachers. The data were analysed thematically. This study was guided by Vygotsky’s sociocultural theory of development which identifies language, society, and culture as the primary aspects of the development of a child. The social interactions that a child has with people living in a particular environment with particular languages strongly shapes the development of cognitive abilities in the child. The findings showed that pre-service teachers lacked sufficient competencies in the teaching of mother tongue literacy. Additionally, the classroom arrangement and teaching approaches that were used by the pre-service teachers were ineffective for learning. Furthermore, the learning materials and pedagogical practices were likely to inhibit successful learning. The implication of this is that the quality of education and learning was compromised. This paper recommends that pre-service teachers should be equipped with skills to teach the mother tongue programme while using relevant and appropriate teaching strategies and learning resources to enhance mother tongue learning of the Oshindonga and Oshikwanyama dialects.